2022
DOI: 10.1002/tesq.3204
|View full text |Cite
|
Sign up to set email alerts
|

“I Don't Let What I Don't Know Stop What I Can do”—How Monolingual English Teachers Constructed a TranslanguagingPre‐KClassroom in China

Abstract: Guided by translanguaging pedagogy, this study examines how monolingual English teachers in a Pre‐K school in China navigate between English and Chinese to construct a translanguaging classroom. Findings based on classroom observations and interviews reveal that, despite being constrained by their monolingualism, the English teachers enacted translanguaging in multiple ways creating three translanguaging components: translanguaging assistance, translanguaging assessment, and translanguaging showcases. Translan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Upon closer examination of the detailed information regarding the clusters presented in Table 6, it is noteworthy that the most frequently cited article in the top five clusters is the same, namely, the work of Bonacina-Pugh et al (2021). Additionally, the most frequently cited article in the remaining three clusters is also the same, namely, the work of Shi and Rolstad (2022). It is important to note that these two articles are not visually represented in Figure 5, which depicts a co-citation network.…”
Section: Key Authorsmentioning
confidence: 99%
“…Upon closer examination of the detailed information regarding the clusters presented in Table 6, it is noteworthy that the most frequently cited article in the top five clusters is the same, namely, the work of Bonacina-Pugh et al (2021). Additionally, the most frequently cited article in the remaining three clusters is also the same, namely, the work of Shi and Rolstad (2022). It is important to note that these two articles are not visually represented in Figure 5, which depicts a co-citation network.…”
Section: Key Authorsmentioning
confidence: 99%
“…This pedagogical approach, advocating the holistic utilization of students' linguistic resources, has recently been embraced in classrooms to address the shift from monolingualism to multilingualism (Cenoz & Gorter, 2020; Fang et al., 2022; García, 2019). Pedagogical translanguaging has been discussed extensively over the past decade in bilingual and multilingual education (Ou et al., 2022) and gained momentum in language learning, especially for English as a foreign or second language education (Shi & Rolstad, 2022). It informs more flexible pedagogies and classroom language practices, allowing for a deeper understanding of learning content (Gu et al., 2022; Nie et al., 2022), effectively maneuvering the multilingual and multimodal repertories to facilitate learning (Fang et al., 2022; García & Li, 2014), enhancing students’ engagement in the classroom (García et al., 2017; Nie et al., 2022), integrating out‐of‐school knowledge into the class to facilitate teaching and learning (Li, 2014; Tai & Li, 2020), and supporting students’ bilingual identities (García et al., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an another type of translanguaging classroom, where monolingual English speaking teachers teach English to Chinese students, Shi and Rolstad (2022) observed that translanguaging can still be used to bolster the students' learning experience. The teachers being observed by Shi and Rolstad (2022) use some techniques that have been described above by Mary and Young (2017) as well as some different ones. For example, when a student had difficulty in understanding something or expressing themselves, the teachers asked the other students to help out in their stronger language.…”
Section: Books Published Bymentioning
confidence: 99%
“…Another example was that one of these teachers asked the students to become the teachers. Shi and Rolstad (2022) argued that "Through reversing the roles of teacher and student, Daniel built rapport with Chinese-English bilingual children, appreciating their translanguaging, while also maximizing their English exposure." (p. 19).…”
Section: Books Published Bymentioning
confidence: 99%